Cambios en la diversidad y variación interanual de la abundancia del zooplancton de un lago somero urbano de La Pampa - Echaniz, Santiago Andrés (2012)
Don Tomás is an urban, turbid and hypereutrophic shallow lake located in the west side of Santa Rosa. As it has an important silverside population (Odontesthes bonariensis) this lake is important for recreational and touristic activities. As many changes in many limnological parameters were observed, including zooplankton composition and abundance between 1995-96 and 2006, the main objective of this research was to compare these parameters with the ones obtained from September 2008 to August 2009. Salinity decreased along the three periods from 1.65 (1995-96) to 0.65 g.l-1 (2008-09) mainly due to the city runoff and the constant water pumping for irrigation. Water transparency also decreased from 0.24 (1995-96) to 0.14 m (2008-09). Zooplankton total richness did not change, but changes in taxonomical composition were observed when groups were separately analyzed (cladoceran richness decreased and rotifers increased during 2006. Cladoceran richness decreased from 9 species in 1995-96 to 4 in 2006, to only 2 species in 2008-2009. The same pattern was observed with copepod richness which decreased from 4 species in 2006 to only 2 species in 2008-09. Rotifer richness, on the other hand, increased from 8 species (1995-96) to 15 (2008-2009). The decreased water transparency could have been due to the lack of Daphnia (observed only in 1995-96) and the increased dominance of rotifers. Total zooplankton abundance showed important inter-annual differences, being the lowest in 2006. The obtained results reveal the wide variability of zooplankton in this type of environment.